Análise geoecológica do município de Fortim-Ceará: contribuições para a proteção ambiental e o desenvolvimento local - Guerra, Fábio Soares (2024)
The municipality of Fortim, located on the east coast of the state of Ceará, presents a varied set of landscapes in which the relationship between society and nature has caused significant changes, both in natural and social terms. Therefore, a geoecological analysis of the aforementioned spatial area is necessary, so that effective contributions can be made to the protection of natural resources and local-based development. With this aim, the research in question aimed to carry out a geoecological analysis of the municipality of Fortim, to develop an environmental-functional zoning proposal and the projection of landscape scenarios, through the integrated geoecological diagnosis of the territory. So much so, the assumptions of Geoecology of Landscapes were used as a theoretical and methodological approach. From this perspective, the landscape was understood as a multidimensional totality, anchored in the tripod: nature, society and culture. The geosystem was used as a spatial unit of operation with a dialectical and holistic character. The method used followed the dialogical, dialectical and integrative perspective through the bias of systemic complexity. Guided by the epistemological basis of Geoecology of Landscapes, the methodological framework of the research followed the following phases: organization and inventory, analysis, diagnosis and proposition. As results and discussion, geoenvironmental and socioeconomic conditions were identified, characterized and correlated. From then on, it was possible to highlight and analyze the geoecological units of Fortim, namely: coastal sea, beach and post-beach, dune field, marine terraces, fluviomarine plains, fluvial and/or fluviolacustrine plains and the pre-coastal plateau. The geoecological framework highlighted made it possible to carry out an integrated landscape diagnosis for the municipality of Fortim, which revealed the resulting problems and impacts, the levels of degradation (environmental impacts), the environmental status and environmental situation, the potentialities and limitations of each geoecological unit. The geoecological diagnosis generated the necessary foundation for the elaboration of proposals for environmental protection and local-based development for Fortim, such as environmental-functional zoning, the action plan and environmental management measures, as well as the projection of landscape scenarios trends and proposals elaborated. Therefore, it is concluded that the municipality of Fortim needs constant studies and work, aimed at planning and environmental management so that the territory can be organized and landscapes managed with equity and justice, with sustainable development as a possible horizon.